Bursal transcriptome of different inbred chicken lines following infection with very virulent infectious bursal disease virus - Mohd Isa, Noor Farhanah; Bejo, Mohd Hair; Mat Isa, Nurulfiza; Ideris, Aini; Nair, Venugopal; Omar, Abdul Rahman (Faculty of Veterinary Medicine, Universiti Putra Malaysia, 2015)
Infectious bursal disease virus (IBDV) targeting IgM-bearing B cells in the bursa of fabricius cause an immunosuppressive effect in young chickens. Infection with IBDV evoked necessary immune response such as infiltration of T cell and macrophages into the bursa which may limit viral replication or promote bursal tissue damage through cytokine secretion. However, mechanisms of very virulent (vv) IBDV infection in chickens of different genetic backgrounds are poorly characterized. Therefore, this study aims to profile transcriptome expression of bursal tissues of inbred chickens with varying genetic background following infection with vvIBDV using RNA-seq Illumina platform in an effort to have a better understanding in host-pathogen interaction. From six infected chicken lines, four has been determined to be highly susceptible while the remaining two is less susceptible based on viral load quantification. Bursal transcriptome profiling result shows that more than 4,500genes has been identified to be significantly expressed with expression value was based on cut off value; log2 fold-change < -2 or log2 fold-change > 2and q-value < 0.05. Genes that were up-regulated after IBDV infection are those involve in immune regulatory network such as pro-inflammatory cytokines and chemokines, JNK-p38 MAPK signalling genes, and stress-response genes. On the other hand, genes that were down-regulated are those involve in DNA replication, and transcription and translation process. This study has enable us to resolve susceptibility level of various chicken lines and evaluation of bursal transcriptome profile allow us identify possible gene involve in host susceptibility.